2007
DOI: 10.1080/01443610601056418
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative assessment of deep myometrial and cervical invasion in endometrial carcinoma: Comparison of magnetic resonance imaging and histopathologic evaluation

Abstract: SummaryThis study aimed to evaluate the accuracy of magnetic resonance imaging (MRI) in the detection of deep myometrial invasion and cervical extension by endometrial carcinoma. This prospective study included 101 patients with histologically documented endometrial carcinoma, between July 1998 and April 2004. The findings of preoperative pelvic MRI were compared with histological diagnosis. From 101 cases studied by pelvic MRI, 43 were classified as deep myometrial invasion (50% of myometrium), where the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…Two recent studies that investigated the accuracies of MRI for estimation of deep myometrial invasion determined the diagnostic accuracies as 81% and 90%. 5,21 The diagnostic accuracy of MRI (85%) in the present study was in accordance with literatures for prediction of deep myometrial invasion. Yamashita et al 9 have reported that MRI findings are incorrect usually in patients with adenomyosis, an intramural or subendometrial myoma, a polypoid tumor, a thin atrophic myometrium, or an atrophic junctional zone between the endometrium and the myometrium.…”
Section: Discussionsupporting
confidence: 91%
“…Two recent studies that investigated the accuracies of MRI for estimation of deep myometrial invasion determined the diagnostic accuracies as 81% and 90%. 5,21 The diagnostic accuracy of MRI (85%) in the present study was in accordance with literatures for prediction of deep myometrial invasion. Yamashita et al 9 have reported that MRI findings are incorrect usually in patients with adenomyosis, an intramural or subendometrial myoma, a polypoid tumor, a thin atrophic myometrium, or an atrophic junctional zone between the endometrium and the myometrium.…”
Section: Discussionsupporting
confidence: 91%
“…For diagnosis of cervical invasion, sensitivity and specificity of MRI range from 50% to 72% and from 90% to 100%, respectively [9][10][11]. The diagnostic value of MRI for presurgical identification of patients at risk of lymph node metastasis, based on myometrial infiltration and cervical invasion of endometrial cancer, has not been reported.…”
Section: Discussionmentioning
confidence: 95%
“…In many institutions, MR imaging has become a standard method. Sensitivity reported for this technique ranges from 80% to 91% (16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Contrast material-enhanced magnetic resonance (MR) imaging is considered the most reliable method and has an accuracy ranging from 62% to 95% (14)(15)(16)(17)(18)(19)(20). However, MR imaging is costly, has limited availability, and cannot be performed in all patients.…”
mentioning
confidence: 99%